Branding as a Tool of Advertisement in Hotels in Kabale Town: A Case Study of Gorilla Trek Camp. - Asiimwe, Elton (Kabale University, 2023)
The study was about the effects of branding as a tool advertising in gorilla trek camp hotel in kabale town. It was based on the following objectives; To identify branding strategy that fits and is specific for gorilla trek camp, to implement the strategies, evaluating if the strategies implemented can work out. A descriptive survey design was used whereas questionnaires and interviews were used to gather data from the respondents. The study findings indicate that business cards, custom t-shirts, aprons, meal menus, brochures, stickers and calendars are commonly used as branding tools in gorilla trek cam while electronic advertising, is rarely used as a branding tool in gorilla trek camp. Improving the brand identity and creating a wide market are the roles of branding in gorilla trek camp. The researcher recommended that the management of gorilla trek camp should plan about embracing such branding strategies like introducing custom t-shirts and identity cards for workers. They should further introduce business cards to distribute to clients in order for the loyal clients to spread the business brand to other people, and more to that they should introduce a logo for the company such that it can be easily identified.